Effect Of Automobile Product Recall On Stock Price Performance - Ngwakwe, Collins (Acta Universitatis Danubius. Œconomica, 2023)
automobile product recall has increased in recent years albeit attendant impact on stock price. Objective: the objective of this paper is to analyse the stock price effect and the stock price response time to automobile product recall for Toyota, GM and Tesla. Prior Work: the paper inclines on prior work on efficient markets and product recall effects on corporate financial value but takes a slightly different stance to focus on automobile recall effect on stock price and reaction time gap. Approach: the paper applied a t-test statistics for difference in mean stock price following automobile product recall announcements. Results: the results show that following the recall announcements, the stock prices reacted negatively at a highly significant value of P<0.05 for all the three industries. Furthermore, following the announcement of recall, it took a day (for Toyota) and three days (for GM and Tesla) for the stock prices to be affected. Implication: the result provides a practical implication for investors to understand when to sell and buy stocks and to automobile industries to manage stock price risk during planned product recall. The paper offers a current case study for university business schools and provides agenda for furthering research on timing of stock price impact after automobile recall. Value: the paper reveals that (within the confines of this study) automobile product recall may take between a day and three days to influence a stock price shock.